This is us. The complete fifth season [videorecording (DVD)] - Fogelman, Dan (20th Century Studios, 2021)
Full of heartfelt wit, drama, and tears the journey of the Pearson family continues in Season Five of this highly acclaimed, award-winning series. With its trademark storytelling style, moving from the past to the future and back again, this season-like-no-other brilliantly incorporates current real-life challenges from the Covid crisis to the complexities of race. Randall pursues the mystery of his birth mother with Beth at his side, Kevin and Madison navigate their relationship while they navigate becoming parents, and Kate and Toby face their relationship and parenting triumphs and challenges. And Rebecca continues to bravely face what could be her biggest challenge ever. Compelling and surprising, it reveals how seemingly tiny events can impact who we become and can transcend time, distance, and even death.